An Integrative Approach to Regional Water Resource Management in Kebumen, Indonesia Through Dynamic Systems Modeling - Wong, Phoenix; Moeis, Armand O. (International Journal Labs, 2025)
The imbalance between water availability and demand, the predominance of agriculture as the main water user, and limited storage infrastructure present major challenges for water resource management in Kebumen Regency, Central Java. This study adopts an integrative approach based on system dynamics modelling to design and analyze adaptive and sustainable water management strategies. The process includes identifying key variables, processing secondary data, and constructing causal loop and stock-flow diagrams to develop simulations of various water management scenarios, taking into account hydrological, social, economic, and environmental aspects. Simulation analysis indicates that developing food crops with low water requirements contributes most significantly to the sustainability of water availability, while increased rainfall does not automatically enhance water supply due to infrastructure constraints. These findings underscore the necessity of integrating agricultural policies, strengthening infrastructure, and implementing adaptive-holistic water resource management to address future water availability challenges.